Rapid diagnosis of beta-haemolytic streptococcus group B endocarditis by buffy-coat examination and gas-liquid chromatography. Issue 8 (August 1979) - Maliwan, N; Reid, R; Katzen, R
Abstract : A semicomatose 34-year-old man had fever, heart murmur, and multiple gangrenous lesions. Several blood cultures were negative. Cultures of the heart valve grew beta-haemolytic streptococcus group B. The organism was seen in buffy-coat examination of the venous blood. The gas-liquid chromatogram of the serum was different from those of normal controls and of patients with invasive candida infection; it closely mimicked the one obtained from the organism itself. These studies promise to be valuable diagnostic adjuncts.